2016
DOI: 10.1371/journal.pone.0156719
|View full text |Cite
|
Sign up to set email alerts
|

Structure of the Plexin Ectodomain Bound by Semaphorin-Mimicking Antibodies

Abstract: Semaphorin family proteins act on cells to mediate both repulsive and attractive guidance via binding to plexin family receptors, thereby playing fundamental roles in the morphogenesis and homeostasis of various tissues. Although semaphorin-plexin signaling is implicated in various diseases and is thus a target of intensive research, our mechanistic understanding of how semaphorins activate plexins on the cell surface is limited. Here, we describe unique anti-plexin-A1 antibodies that can induce a collapsed mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
23
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 34 publications
1
23
0
Order By: Relevance
“…It is generally believed that semaphorin-induced plexin dimerization is the key event during the cell signaling. Very recently, we and others (Suzuki et al, 2016;Kong et al, 2016) have discovered that the entire plexin ectodomain assumes a highly unusual ''C-shape,'' and suggested that a particular type of plexin dimer arrangement can elicit a positive signal. It is therefore possible that binding of PB1m6 may not only modulate the ligand affinity but also regulate the conformation of the entire PlxnB1 ectodomain on the cell surface, resulting in an efficient signal suppression.…”
Section: Discussionmentioning
confidence: 86%
“…It is generally believed that semaphorin-induced plexin dimerization is the key event during the cell signaling. Very recently, we and others (Suzuki et al, 2016;Kong et al, 2016) have discovered that the entire plexin ectodomain assumes a highly unusual ''C-shape,'' and suggested that a particular type of plexin dimer arrangement can elicit a positive signal. It is therefore possible that binding of PB1m6 may not only modulate the ligand affinity but also regulate the conformation of the entire PlxnB1 ectodomain on the cell surface, resulting in an efficient signal suppression.…”
Section: Discussionmentioning
confidence: 86%
“…Recent structural studies of the intact extracellular region of class A plexins in the apo state show that the three PSI domains and six IPT domains together adopt a highly curled shape, leading to an overall ringlike architecture 14,15 . Based on these structures, a docking model of the entire extracellular region of class A plexins in complex with semaphorin has been constructed, showing that the ring-shape of plexin brings the two copies of the membrane-proximal IPT6 domain in the dimeric complex to close proximity, compatible with the formation of the intracellular active dimer 14,15 . Classes B and D plexins may use the same mechanism, as their extracellular regions have the same domain composition as class A plexins.…”
mentioning
confidence: 99%
“…The extracellular domain of several plexins has been shown to adopt different conformations ranging from a nearly closed, ring-like form to a more-open, chair-like form 17,47,48 . Very recently, a particular plexin, Plexin-D1, has been reported to sense shear stress-induced mechanical forces in endothelial cells 17 .…”
Section: Discussionmentioning
confidence: 99%